Terminus dynamics at an advancing glacier: Taku Glacier, Alaska - Truffer, M; Motyka, RJ; Hekkers, M; Howat, IM; Matt King (2009)
Taku Glacier, Alaska, USA, is currently in the advance stage of the tidewater glacier cycle. We investigated the near-terminus dynamics by measuring surface velocities, surface elevation changes, ice thickness and ablation. Velocities vary on sub-daily, diurnal, seasonal and interannual timescales. Flowline modeling shows that the modeled surface velocities are sensitive to changes in till yield strength and thus effective basal pressures. The glacier bed deepens in the up-glacier direction and this imposes a minimum subglacial water pressure necessary for water to drain along the bed. In a simple model we impose water-pressure gradients based on phreatic surfaces of constant slopes to simulate the wintersummer transitions. This proves sufficient to explain an observed early-season switch from compressional to block flow. Velocities also vary between years. Changing basal conditions can result in lower horizontal velocities, which decrease the ice supply to the terminus and result in temporary surface lowering. But a decrease in ice flux to the terminus must lead to ice storage further upstream, and that ice mass will eventually reach the terminus. This can explain the observed episodic nature of terminus advance.